2016
DOI: 10.18632/oncotarget.8295
|View full text |Cite
|
Sign up to set email alerts
|

Chronic TGFβ stimulation promotes the metastatic potential of lung cancer cells by Snail protein stabilization through integrin β3-Akt-GSK3β signaling

Abstract: Chronic exposure to TGFβ, a frequent occurrence for tumor cells in the tumor microenvironment, confers more aggressive phenotypes on cancer cells by promoting their invasion and migration while at the same time increasing their resistance to the growth-inhibitory effect of TGFβ. In this study, a transdifferentiated (TD) A549 cell model, established by chronically exposing A549 cells to TGFβ, showed highly invasive phenotypes in conjunction with attenuation of Smad-dependent signaling. We show that Snail protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…It was previously reported that miR-18-mediated low-expression of target gene TGF-β intimately contributed to prolonged survival of glioblastoma multiforme (GBM) patients 55 . Similarly, miR-19 could exhibit modulatory effect on GSK-3β/β-catenin axis, down-regulated target gene GSK-3β could promote the metastatic potential of lung cancer cells, revealing a poor survival outcome for cancer patients 56 , 57 . Besides, miR-20a was able to suppress the hepatocellular cancer cell proliferation and migration by directly targeted RUNX3, while clinical evidences have proved that RUNX3 was negatively associated with tumor progression, lymph node metastasis and poor prognosis 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that miR-18-mediated low-expression of target gene TGF-β intimately contributed to prolonged survival of glioblastoma multiforme (GBM) patients 55 . Similarly, miR-19 could exhibit modulatory effect on GSK-3β/β-catenin axis, down-regulated target gene GSK-3β could promote the metastatic potential of lung cancer cells, revealing a poor survival outcome for cancer patients 56 , 57 . Besides, miR-20a was able to suppress the hepatocellular cancer cell proliferation and migration by directly targeted RUNX3, while clinical evidences have proved that RUNX3 was negatively associated with tumor progression, lymph node metastasis and poor prognosis 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, TGF-β promotes breast cancer cells motility and metastasis by upregulating the gene expression of integrins. 128,129 Another example is in hepatoma carcinoma environment, TGF-β enhanced cell migration and invasion by increasing the gene expression of chemokine receptors. 130 In conclusion, the promotion of TGF-β signaling on tumor development lies largely on the increased angiogenesis, decreased immune performance and more regular extra-cellular architecture.…”
Section: Tgf-β Dependent Signaling Pathwaymentioning
confidence: 99%
“…The inhibition of heat-shock protein 27 (HSP27), highly expressed in fibrotic foci of idiopathic pulmonary fibrosis (IPF), results in Snail degradation followed by inhibition of TGF-b1 induced cell transition [75]. TGF-b1 stabilizes Snail and is associated with increased integrin b3 with consequent high Akt activity and elevated inhibitory phosphorylation of GSK-3b [76,77].…”
Section: Tgfmentioning
confidence: 99%